Differently PEGylated Polymer Nanoparticles for Pancreatic Cancer Delivery: Using a Novel Near-Infrared Emissive and Biodegradable Polymer as the Fluorescence Tracer - Cai, Huazhong; Chen, Yanxia; Xu, Liusheng; Zou, Yingping; Zhou, Xiaoliang; Liang, Guoxin; Wang, Dongqing; Tao, Zhimin (Frontiers in Bioengineering and Biotechnology, 2021)
In this study a chemically synthetic polymer, benzo[1,2-b:4,5-b’]difuran(BDF)-based donor-acceptor copolymer PBDFDTBO, was individually coated by amphiphilic poly(ethylene oxide)-block-poly(ε-caprolactone) (PEO-PCL) and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxy(polyethylene glycol) (DSPE-PEG or PEG-DSPE), to form stably fluorescent particles at nano dimension in the near-infrared (NIR) window. The physicochemical properties of synthesized nanoparticles were well characterized and compared, including their size, morphology, and surface charge. Cell viability using two pancreatic cancer cell lines was examined in the presence of PBDFDTBO-included PEGylated nanoparticles. In subcutaneous murine cancer models both polymeric nanoparticles exhibited prolonged circulation time, desired tumor accumulation, and preferred biodistribution, showing great biodegradability and biocompatibility. Nevertheless, with the same PEGylated surface, hydrophobic segments that anchor on the encapsulated PBDFDTBO core affected the biodistribution and tumor accumulation of nanoparticles, to a degree relying on the hydrophobic interactions between hydrophobic ends of amphiphilic polymers (DSPE or PCL moiety) and the enwrapped PBDFDTBO. Both PEGylated nanoparticles were compared to derive an optimized coating strategy for a desired biological feature in pancreatic cancer delivery.